A close-up of bibliographic coupling on organizational communication in sports research - Abdullah, Khairul Hafezad; Sofyan, Davi; Rojo, Jeferson Roberto; Hammood, Waleed Abdulmaged (Manajemen Komunikasi, 2022)
The emergence of sport sociology related to sport and communication spurred a gradual entry into academic research. This study uses bibliometric analysis of bibliographic coupling, a phenomenon that occurs when two texts quote the same source. The purpose of this study is to explore publishing trends using the unit of analysis bibliographical coupling on organizational communication in sports. The results indicated that 419 publications had been indexed in the Scopus database between 1981 and 2022. Articles were the most common document published in the database, accumulating 265 papers. Social Sciences is the most significant subject area, with 214 records. A paper written by Winand et al. in 2019 entitled “International sports federations’ social media communication: A content analysis of FIFA’s Twitter account” has become a document that obtained more citations accruing a total strength of 91. Notably, this analysis alludes that the International Journal of Sport Communication has become the most multiple credentials, with 240 citations. Two scholars, Anagnostopoulos, C. and Chadwick, S., were credited as successful authors. Griffith University, from Australia, advanced 67 citations. The United States became the leading country with total link strength of 3876. It can be concluded that research on this topic is expanding due to the empowerment of research methodologies and the development of new research contributions in the form of new avenues. Researchers and practitioners can increase future understanding in this field by thoroughly examining sports communication in numerous research areas.